2019
DOI: 10.1152/ajpgi.00080.2018
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cholesterol and apolipoprotein A-I are trafficked in endosomes and lysosomes in the live zebrafish intestine

Abstract: Difficulty in imaging the vertebrate intestine in vivo has hindered our ability to model nutrient and protein trafficking from both the lumenal and basolateral aspects of enterocytes. Our goal was to use live confocal imaging to increase understanding of intestinal trafficking of dietary cholesterol and apolipoprotein A-I (APOA-I), the main structural component of high-density lipoproteins. We developed a novel assay to visualize live dietary cholesterol trafficking in the zebrafish intestine by feeding TopFlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Zebrafish and mammals share considerable overlap in major organs and in key nodes of metabolic control such as insulin signalling and appetite regulation 1–3 . Transgenic zebrafish with tissue-specific fluorescence have been implemented in studies of pancreatic β-cell regeneration 4 , dietary cholesterol trafficking 5 , gluconeogenesis 6 , and iron metabolism 7 , while recent advances in targeted mutagenesis have contributed to the rise in zebrafish models of metabolic disorders 811 .…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish and mammals share considerable overlap in major organs and in key nodes of metabolic control such as insulin signalling and appetite regulation 1–3 . Transgenic zebrafish with tissue-specific fluorescence have been implemented in studies of pancreatic β-cell regeneration 4 , dietary cholesterol trafficking 5 , gluconeogenesis 6 , and iron metabolism 7 , while recent advances in targeted mutagenesis have contributed to the rise in zebrafish models of metabolic disorders 811 .…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression of apoab, but not apoa1a, was significantly induced by BDE-47, a response attenuated in co-exposure with high PS. The apolipoprotein genes apoa1a and apoba are comparatively well-characterized in early zebrafish development ( Otis and Farber, 2016 ; Otis et al, 2019 ; Thierer et al, 2019 ; Templehof et al, 2021 ) and have been shown to be responsive to feeding status ( Cruz-Garcia and Schlegel, 2014 ) and contaminants including BPA and PFOS as well as their replacement compounds BPS and F-53B ( Sant et al, 2017 ; Wang W et al, 2018 ; Shi et al, 2019 ; Martínez et al, 2020 ). Gene expression of apoba is, similarly to apoa1a ( Babin et al, 1997 ) , strongly induced in the yolk syncytial layer at 2 dpf ( Thierer et al, 2019 ; Templehof et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is a limitation of the FPLC method we have used for the sample preparation. For the fasted experiment, we assumed that the main source of apoA-I was the liver but we cannot exclude an intestinal production as suggested in animal models 14,15 . Then, we can only estimate the production related to the meal stimulation.…”
Section: Discussionmentioning
confidence: 99%